THE CONCEPT OF COUNTRY AND LEADERSHIP IN ISLAMIC POLITICAL PHILOSOPHY OF IBN TAIMIYAH - Hasan Basri; Matroni Matroni (JURNAL SETIA PANCASILA, 2022)
The caliphate discourse promoted by several groups of Islamic fundamentalist movements is no longer able to fulfill the goals of government in Islam. Ibn Taimiyah finally promised an Islamic political theory which was expected to be able to cover the shortcomings and limitations of the caliphate theory by referring to the classical caliphate theory. Ibn Taimiyah's political theory is contained in one of his works entitled al-Siyasah al-Syar'iyah fi islah al-Ra'i wa al-Ra'iah (Politics Based on Sharia for the Improvement of Returners and Shepherds). The existence of the historical background of the Khulafa al-Rasyidin's caliphate is nothing more than an accident, not an example of political life. Even the life of the Prophet is not seen as a basis for government that needs to be adopted in a particular political system of government, it is nothing more than a sui generis institution, not as a basis for Islamic politics. Ibn Taimiyah's rejection of historical practice as the basis of political philosophy, then Ibn Taimiyah avoided the mistake of assessing existing political power as power that was legalized by the shadow of the caliph, as was found in the characteristics of previous political theories of thought..